1997
DOI: 10.1021/ie950654u
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Neutralization Control Based in Fuzzy Logic:  Simulation Results

Abstract: Neutralization is a technique widely used as a part of wastewater treatment processes. Due to the importance of this technique, extensive study has been devoted to its control. However, industrial wastewater neutralization control is a procedure with a lot of problemsnonlinearity of the titration curve, variable buffering, changes in loadingand despite the efforts devoted to this subject, the problem has not been totally solved. In this paper, the authors present the development of a controller based in fuzz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 7 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…A self-tuning controller is described in Babuska et al (2002). Adaptive nonlinear control strategies (Henson and Seborg, 1994), modelbased (Sing and Postlethwaite, 1997) and fuzzy logic controllers (Garrido et al, 1997) have also been used.…”
Section: Introductionmentioning
confidence: 99%
“…A self-tuning controller is described in Babuska et al (2002). Adaptive nonlinear control strategies (Henson and Seborg, 1994), modelbased (Sing and Postlethwaite, 1997) and fuzzy logic controllers (Garrido et al, 1997) have also been used.…”
Section: Introductionmentioning
confidence: 99%
“…In this test the controller was evaluated using a simulation run where the process gain changed throughout the course of the simulation. To simulate the behavior of the pH evolution throughout the experimental runs, a mathematical model was developed based on that proposed by Garrido et al (1997). This model was refined in order to have the possibility of reproducing the experimental conditions of dead times and specific water compositions.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a numeric output is obtained (Kosko, 1992;Cox, 1994). Garrido et al (1997) compared the application of a fuzzy controller with the advanced controllers proposed by Riggs et al (1990), Gaulian et al (1990), and Kurtz (1985). Results obtained showed that FLC could be considered a valuable tool in the wastewater neutralization processes testing them in computer simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Model-based fuzzy controllers, namely an internal model controller (Postlethwaite, 1994), nonlinear model predictive controller (Peng and Jang, 1994), a relational model based controller (Sing and Postlethwaite, 1996), and a dynamic fuzzy learning controller (Venkateswarlu and Gangiah, 1996), are also reported for different chemical processes. Recently, Garrido et al (1997) applied a rule-based fuzzy logic controller for wastewater neutralization. This considers only input concentration changes in acid wastewater to maintain its pH at 7.…”
Section: Introductionmentioning
confidence: 99%